Racial Prejudice And Assimilation In Jhumpa Lahari's The Namesake(2003): A Sociological Approach - Nugroho, Acep; , Dr. Phil dewi Chandraningrum; , Titis Setyabudi, S.S. M. Hum (2015)
This study is about racial prejudice and assimilation. The problem of this study is racial prejudice and assimilation is reflected in Jhumpa Lahiri's The Namesake. The object of the study is The Namesake novel by Jhumpa Lahiri. It used sociological approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is The Namesake novel and the secondary data source is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusion. Based on the analysis it is clear that there is a close relation between structural analysis of this novel and social reality in America in early twenty first century. Jhumpa Lahiri wants to show the racial prejudice and assimilation in America in the early twenty first century through The Namesake novel.